Removal and Recovery of Lead Ions from Wastewater of Lead-Acid Secondary Battery by a Hybrid Process Containing of Complexation-Ultrafiltration-Electrolysis - Zhang, Yongfeng; Bai, Jie; Cui, Jingdong; Wu, Fei; Wang, Hua (Asian Journal of Chemistry, 2011)
A multi-stage process has been studied at pilot scale for the removal and recovery of lead from wastewater of a lead-acid secondary battery plant. In the treatment with a hybrid process of complexation-ultrafiltration-electrolysis, at first, Pb2+ ion is absorbed by polyacrylic acid and complexated into compounds. These compounds, which then become bigger than the pore size of the selected membrane in the ultrafiltration, can be retained and concentrated, whereas water of permeate is then purified from the feed solutions. Then Pb2+ ion is desorbed from the concentrated solution under the acid conditions. After second ultrafiltration process Pb2+ ion is separated from the polyacrylic acid. Finally the lead is recovered from the acid solution by electrodeposition.